Nikolaos Louros (1898–1986) the reformer of Greek obstetrics and gynaecology of the 20th century - Manidaki, Anna G.; Tsiligianni, Ioanna; Trompoukis, Constatinos (2018)
The present article reports on the career of Professor Nikolaos Louros and his contribution to the development of obstetrics and gynaecology. The data presented is based on desk research with the aim to gather and analyse relevant credible information from documents existing in primary and secondary resources in the archive of Foundation History of Medicine N. Louros. As a Professor at the University of Athens, Louros introduced new teaching methods. His multifaceted work includes writing, teaching, research, and the clinical and laboratory context. His scientific interest covers all areas of obstetrics and gynaecology. Pioneering and progressive in the medical field, he invented new clinical and surgical methods with international appeal. As a director, Louros established innovative rules in the Maternity Hospitals he directed. He supported every effort aiming to protect maternity and the child, and adopted a new approach regarding the problem of home based obstetric help to the destitute women.
Članak govori o karijeri profesora Nikolaosa Lourosa i njegovu doprinosu razvoju opstetricije i ginekologije. Prikazani podaci prikupljeni su na temelju desk-istraživanja s ciljem analiziranja relevantnih vjerodostojnih podataka iz dokumenata koji se nalaze u primarnim i sekundarnim izvorima u arhivi Zaklade povijesti medicine N. Louros. Kao profesor na Sveučilištu u Ateni Louros je uveo nove metode poučavanja. Njegov višestruki rad uključuje pisanje, poučavanje i istraživanje te klinički i laboratorijski kontekst. Njegov znanstveni interes obuhvaća sva područja opstetricije i ginekologije. U medicinskom području iznimno inovativan i progresivan, izumio je međunarodno prihvaćene nove kliničke i kirurške metode. Kao ravnatelj Louros je uveo inovativna pravila u rodilišta kojima je upravljao. Podržao je sve napore usmjerene zaštiti materinstva i djeteta i uveo nov pristup problemu kućne opstetricijske pomoći siromašnim ženama.
Bibliografske bilješke uz tekst ; bibliografija: 20 jed.
Sažetak
Keywords: Povijest medicine -- Ginekologija -- Porodništvo; Louros, Nikolaos